Human rights education : forging an academic discipline - Cargas, Sarita (Pennsylvania studies in human rights., 2020)
Sarita Cargas contends that the field of human rights should be treated as an academic discipline in higher education contexts, possessing as it does a canon of literature, a community of scholars, and a methodology. Her book offers practical recommendations for creating human-rights programs at the university level in the United States.